Analysis of the Function of Erotsis Language Style in the White Novel Work Tere Liye - Ade Rahima (Socrates: Journal of Education, Philosophy and Psychology, 2026)
This research is motivated by the author's desire to conduct collaborative research between language and literature, which are scientific disciplines. which the author is currently pursuing. Therefore, the author conducted research on the function of erotesis language style which is examined in the novel Si Putih by Tere Liye. The purpose of this research is to describe the use of erotesis language style function found in the novel Si Putih by Tere Liye. To conduct this research, the author used the method This is a qualitative descriptive study. The data in this study consist of quotations from findings about the function of erotesis in this novel. In the form of this quote, the author analyzed it using Keraf's theory so that the author could describe the function of the erotesis style of language contained in this novel. Based on the collection and based on data analysis, the results of this study found 51 quotations related to the function of erotesis in this novel. The function to achieve a deeper effect was found in 21 quotations. Meanwhile, findings regarding the function of providing reasonable emphasis were found in 20 quotations and the function to ask something that does not require an answer was found in 10 quotations. The most dominant quotations are quotations from erotesis which function to achieve a deep effect. From the results of this study, it can be suggested that writing literary stories requires erotesis to emphasize the meaning that is intended to be expressed in a questioning style. So that literary works become enjoyable to read.